2018
DOI: 10.1002/polb.24725
|View full text |Cite|
|
Sign up to set email alerts
|

High‐strength hydrogels: Microstructure design, characterization and applications

Abstract: Hydrogels are a class of polymeric network materials embedded in a water-rich environment. They are widely applied in drug delivery, actuator, and sensor. However, conventional hydrogels encountered limits from their poor mechanical property. Recent researches in hydrogels have been focusing on mechanical enhancement, ranging from design of microstructures to adjustment of compositions in hydrogels. Here, the design and fabrication strategies of high-strength hydrogels, as well as major progress in their typic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 165 publications
(258 reference statements)
2
29
0
Order By: Relevance
“…For example, to seed osteoblast cells, a more rigid material is required than for culturing adipocytes [17]. However, materials characterization, tensile and compressive tests are basic methods for mechanical performance evaluation [18,19].…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…For example, to seed osteoblast cells, a more rigid material is required than for culturing adipocytes [17]. However, materials characterization, tensile and compressive tests are basic methods for mechanical performance evaluation [18,19].…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…This may be due to its relatively poor tensile strength. At a tensile strength of 0.128 MPa, Hussain et al [ 88 ] found their glycogen-derived hydrogel to have an average value amongst the group, and certainly inferior to other biopolymer-derived hydrogels like chitosan and gelatine, as collated in a review by Hua et al [ 88 , 89 , 90 , 91 ]. However, the glycogen-derived hydrogel demonstrated superior elongation at fracture, reaching 810% strain.…”
Section: The History Contemporary Status and Future Applicationsmentioning
confidence: 99%
“…The organogel‐REs possess very good mechanical properties and show an ultrahigh breaking strength of 80 MPa, which surpasses most gel materials. [ 37 , 38 , 39 , 40 , 41 ] By utilizing the luminescent colors of the organogel‐REs as the binary codes of “0” and “1,” information storage and encryption are realized in complex patterns of organogel‐REs, such as self‐information pattern, quick‐response (QR) code and barcode. Information encoded in the apparent patterns could easily be retrieved using a standard decoding program, while information encrypted in the pattern colors could only be deciphered from the color image under 365 nm illumination using a color recognition and shape detection program.…”
Section: Introductionmentioning
confidence: 99%